Genetic analysis of brown planthopper resistance in Thai cultivars, local varieties, and wild relatives of rice using molecular markers - JUTHAPORN SAENGPRAJAK; JIRAPA PHETSOM; APHIDECH SANGDEE; AJIN RATTANAPAN; ARNUSORN SAENGPRAJAK; THANWANIT THANYASIRIWAT; WUTTIPONG MAHAKHAM; PIYADA THEERAKULPISUT (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Saengprajak J, Phetsom J, Sangdee A, Rattanapan A, Saengprajak A, Thanyasiriwat T, Mahakham W, Theerakulpisut P. 2024. Genetic analysis of brown planthopper resistance in Thai cultivars, local varieties, and wild relatives of rice using molecular markers. Biodiversitas 25: 4870-4877. The brown planthopper [Nilaparvata lugens Stål 1854] is prevalent in Asia as a major insect pest that causes significant damage to rice crops. This study aimed to identify cost-effective, eco-friendly methods for developing BPH (Brown Planthopper)-resistant rice varieties by examining the genetic basis of resistance in 40 rice germplasms, including Thai cultivars, local varieties, and wild relatives. Five DNA markers, including SSR (bph2, Bph3, Bph15, Bph17) and InDel (Bph14) markers, closely linked to major BPH resistance genes, were utilized to evaluate genetic diversity. Ten loci, with an average of 2 alleles per locus and 100% polymorphism, were identified. Of the 35 genotypes analyzed, each genotype contained one to five BPH resistance genes. Allele frequencies ranged from 34.92% to 42.86%, while expected heterozygosity varied between 0.242 (RM463) and 0.367 (RM16626), averaging 0.321. The polymorphic information content (PIC) values ranged from 0.388 to 0.437, with an average of 0.419, indicating moderate polymorphism and effective discriminating power for the selected BPH-specific markers. UPGMA analysis grouped the 40 rice genotypes into three main clusters, distinguishing them into resistant and susceptible groups. Our findings provide valuable information for selecting parental lines with BPH resistance, supporting the integration of marker-assisted selection (MAS) into rice breeding programs to develop BPH-resistant varieties.